Renal denervation in comparison with intensified pharmacotherapy in true resistant hypertension: 2-year outcomes of randomized PRAGUE-15 study. Issue 5 (May 2017) - Rosa, Ján; Widimský, Petr; Waldauf, Petr; Zelinka, Tomáš; Petrák, Ondřej; Táborský, Miloš; Branny, Marian; Toušek, Petr; Čurila, Karol; Lambert, Lukáš; Bednář, František; Holaj, Robert; et al.
Abstract : Objectives: The randomized, multicentre study compared the efficacy of renal denervation (RDN) versus spironolactone addition in patients with true resistant hypertension. We present the 24-month data. Methods: A total of 106 patients with true resistant hypertension were enrolled in this study: 52 patients were randomized to RDN and 54 patients to the spironolactone addition, with baseline SBP of 159 ± 17 and 155 ± 17 mmHg and average number of drugs 5.1 and 5.4, respectively. Two-year data are available in 86 patients. Spironolactone addition, as crossover after 1 year, was performed in 23 patients after RDN, and spironolactone addition followed by RDN was performed in five patients. Results: Similar and comparable reduction of 24-h SBP after RDN or spironolactone addition after randomization was observed, 9.1 mmHg ( P = 0.001) and 10.9 mmHg ( P = 0.001), respectively. Similar decrease of office blood pressure (BP) was observed, 17.7 mmHg ( P < 0.001) versus 14.1 mmHg ( P < 0.001), whereas the number of antihypertensive drugs did not differ significantly between groups. Crossover analysis showed nonsignificantly better efficacy of spironolactone addition in 24-h SBP and office SBP reduction than RDN (3.7 mmHg, P = 0.27 and 4.6 mmHg, P = 0.28 in favour of spironolactone addition, respectively). Meanwhile, the number of antihypertensive drugs was significantly increased after spironolactone addition (+0.7, P = 0.001). Conclusion: In the settings of true resistant hypertension, spironolactone addition (if tolerated) seems to be of better efficacy than RDN in BP reduction over a period of 24 months. However, by contrast to the 12-month results, BP changes were not significantly greater. Abstract : Supplemental Digital Content is available in the text